Critical discourse analysis of netizens’ comments on the 2024–2029 presidential and vice-presidential debate based on a corpus - Handayani, Maya Rini; Rahmi, Amelia; Hilmi, Mustofa; Chairullah, Dimas (Islamic Communication Journal, 2025)
Presidential elections constitute a cornerstone of democratic governance, symbolizing the legitimacy and trust vested in government by the populace. The 2024 Indonesian presidential election provided a platform for public participation in shaping the nation's policy trajectory. Recognizing the pivotal role of social media, particularly YouTube, in contemporary campaigns, candidates leveraged these platforms to facilitate public discourse and gauge public sentiment towards presidential and vice-presidential candidates. This study employed a corpus-based approach to analyze netizens' comments during the debates. Through a qualitative methodology, 79,378 comments were collected from eight prominent YouTube channels: KPU RI, CNN Indonesia, INews, RCTI, TVRI, TVOne, Kompas TV, and Metro TV. The analysis draws upon Teun A. van Dijk's Critical Discourse Analysis (CDA) and Stewart L. Tubbs and Sylvia Moss' communication styles. Findings indicate that Anies Baswedan and Muhaimin Iskandar projected an image of academic prowess, intelligence, law-abidingness, and religiosity, while adopting a controlling communication style. In contrast, Prabowo and Gibran were associated with discourses of sincerity, millennial appeal, continuity of Jokowi's programs, and impressiveness. However, this pair exhibited a relinquishing communication style, characterized by passivity and a deferential approach. Finally, Ganjar Pranowo and Mahfud MD presented themselves as visionary, credible, and possessing integrity, employing an equalitarian communication style marked by respect and dialogue. ***** Pemilihan presiden (pilpres) adalah elemen vital dalam demokrasi yang mewakili legitimasi dan kepercayaan rakyat kepada pemerintah. Melalui pilpres Indonesia 2024, masyarakat ikut menentukan kebijakan negara. Para kandidat menyadari pentingnya media sosial, terutama YouTube, dalam kampanye mereka, yang memungkinkan publik untuk menyampaikan pendapat dan mencerminkan sentimen terhadap calon presiden dan wakil presiden. Penelitian ini menggunakan dataset berbentuk korpus yang berisi komentar warganet saat debat berlangsung. Menggunakan metodologi kualitatif, penelitian ini mengumpulkan 79.378 komentar dari channel KPU RI, CNN Indonesia, INews, RCTI, TVRI, TVOne, Kompas TV, dan Metro TV. Kami mengimplementasikan teori Teun A van Djik untuk Analisis Wacana Kritis (AWK), Stewart L Tubbs dan Sylvia Moss untuk gaya komunikasi. Hasil studi ini, Anies Baswedan dan Muhaimin Iskandar menunjukkan pribadi yang akademis, cerdas, taat hukum, dan religius serta bergaya controlling style. Sedangkan ihlas, milenial, melanjutkan program Jokowi, dan impresif merupakan wacana yang terlihat pada Prabowo dan Gibran, namun pasangan ini mengadopsi gaya relinquishing style, yaitu bersikap lebih pasif dan menyerahkan inisiatif kepada lawan debat. Paslon terakhir, Ganjar Pranowo dan Mahfud MD dalam menyampaikan pendapatnya terlihat visioner, kredibel, dan memiliki integritas, selain itu pasangan ini menerapkan gaya equalitarian style, yang mencerminkan sikap saling menghargai dan dialogis dalam menyampaikan pendapat.